LAYANAN BIMBINGAN KELOMPOK TEKNIK CINEMATHERAPHY UNTUK MENURUNKAN KONFORMITAS PERILAKU MEMBOLOS SISWA SMP NEGERI 2 CIPEUNDEUY - Sini Fauziah, Sini Sini Fauziah; Rosita, Tita; Renata Manuardi, Ardian (IKIP Siliwangi, 2024)
The background of this research is the high conformity of truant behavior in class VIII students at SMP Negeri 2 Cipeundeuy. The purpose of this study was to find out the conformity of truant behavior before being given service, the implementation of the service and the effectiveness of group guidance services using the Cinematherapy technique to reduce the conformity of truant behavior in class VIII students at SMP Negeri 2 Cipeundeuy. In this study using the Mix Methode with the explanatory sequential design. This design is the use of two quantitative and qualitative research methods sequentially (sequence). The population of this study was 100 students using a purposive sampling technique, namely 8 students who had a high conformity category based on the results of the pre-test. Quantitative data were collected using a conformity questionnaire for truant behavior, then for qualitative data using observation and interview techniques. The results of this study indicate that the majority are in the medium category, namely 72%, and the implementation of group guidance services using cinematherapy techniques is effective in reducing truant behavior conformity, which originally was in the high category to become low after being given group guidance services using cinematherapy techniques for two meetings.